A Literature Survey on Opportunities and Challenges of Ride-Sharing Services (Al-Qamar, 2024)
Ride-sharing services have revolutionized the way people commute in urban areas. They provide a cost-effective and convenient alternative to traditional transportation options like taxis and public transit. By utilizing technology to connect riders with drivers, these services have made it easier for individuals to get from point A to point B in a timely manner. A literature survey on opportunities and challenges of ride-sharing services reveals a plethora of insights into this rapidly evolving industry. The research points out the numerous benefits that ride-sharing services offer to both consumers and the environment. Furthermore, it sheds light on the challenges that these services face, such as regulatory hurdles and concerns about safety and security. One of the key opportunities highlighted in the literature survey is the potential for ride-sharing services to reduce traffic congestion and alleviate parking shortages in cities. By encouraging carpooling and reducing the number of vehicles on the road, these services have the potential to make urban areas more livable and sustainable.
Keywords: Literature Survey; Opportunities; Challenges